Is educational game effective in improving critical thinking skills? - Nur Fitriyadi; Wuri Wuryandani (Jurnal Prima Edukasia, 2021)
This research is based on a needs analysis of interview result to the fifth-grade elementary school teachers in Kalasan District, Sleman Regency, Yogyakarta Special Region who stated that educational game media was needed to enrich the variety of instructional media and improve students' critical thinking skills. The purpose of this research and development is to produce an appropriate and effective educational game. This product development relies on Borg Gall model which includes ten steps: information gathering, planning, initial product development, limited field trials, product revisions, expanded field trials, product revisions, operational field trials, final product revisions, and dissemination and implementation. Product trials were conducted at SD Negeri Sorogenen 2, SD Negeri Tamanan 1, and SD Negeri Tunjungsari 2 in Kalasan District, Sleman Regency, Yogyakarta Special Region. Practicality test was carried out by implementing questionnaires concerning teachers’ and students’ response after the learning process. Effectiveness test during the field trials was conducted using pretest-posttest questions. The results showed that the developed educational game was suitable for use according to media experts with a score of 85.71 or in ‘Very Good’ category and material experts with a score of 67.50 or in the good category. Based on statistical tests, the educational game was proven to be effective in improving students’ critical thinking skills during the learning process.